Побудова математичної моделі конвективно-теплового осушення пористих тіл в сушильних установках - Бурак, Я.Й.; Гайвась, Б.І. (Моделювання та інформаційні технології, 2010)
In this work the mathematical model is propesed for convektive-thermal drying capillarily porous bodies with taking into account transpiration zone deepening under any thermal time-regime of a drying agent characterized by values of temperature, moisture and fanning speed. The boundary value problem is formulated with allowance for movement of the phase transformation boundary. A methodology is proposed for determination of phase transformation temperature as well as saturation pressure allowing for equations of both state and energy balance. The Caushy problem is formulated for determining a movement law of the phase transition boundary.